ANALISIS KUALITAS DAN NILAI EKONOMIS PELLET KAYU GELAM - Andy Nugraha; Herry Irawansyah; Muhammad; Moh Noer Afifuddin; Rizqi Nor Al’Arisko (Scientific Journal of Mechanical Engineering Kinematika, 2024)
Gelam wood is a natural species in swamp forests and is found in many peat swamp forests in South Kalimantan. Due to the abundant availability of gelam wood raw materials in this region and the need for biomass-based energy, wood pellets from gelam wood can be a solution. In this research, an evaluation was carried out on the quality of gelam wood pellets which included calorific value, specific gravity, and pressure test. In addition, an economic analysis of kayu gelam pellets was also carried out. This study used adhesives in the form of tapioca and wheat flour, variations in adhesive percentages of 0%, 5%, 10%, 15%, and powder sizes of 40 mesh, 50 mesh, and 60 mesh. The results of the research show that the calorific value decreases as the size of the gelam sawdust decreases and tapioca adhesive provides the best calorific value. Larger mesh sizes tend to produce higher compression test values and denser specific gravity. From an economic perspective, gelam wood pellets are relatively cheaper and easier to obtain